COVID-19 and the immune system - Paces, J; Strizova, Z; Smrz, D; Cerny, J (Physiological research, 2020)
A close interaction between the virus SARS-CoV-2 and the immune system of an individual results in a diverse clinical manifestation of the COVID-19 disease. While adaptive immune responses are essential for SARS-CoV-2 virus clearance, the innate immune cells, such as macrophages, may contribute, in some cases, to the disease progression. Macrophages have shown a significant production of IL-6, suggesting they may contribute to the excessive inflammation in COVID-19 disease. Macrophage Activation Syndrome may further explain the high serum levels of CRP, which are normally lacking in viral infections. In adaptive immune responses, it has been revealed that cytotoxic CD8+ T cells exhibit functional exhaustion patterns, such as the expression of NKG2A, PD-1, and TIM-3. Since SARS-CoV-2 restrains antigen presentation by downregulating MHC class I and II molecules and, therefore, inhibits the T cell-mediated immune responses, humoral immune responses also play a substantial role. Specific IgA response appears to be stronger and more persistent than the IgM response. Moreover, IgM and IgG antibodies show similar dynamics in COVID-19 disease.
Keywords: přirozená imunita; Host-Pathogen Interactions; koronavirové infekce; vakcíny proti COVID-19; Betacoronavirus; pandemie; SARS-CoV-2; Immunity, Innate; Viral Vaccines; virová pneumonie; lidé; interakce hostitele a patogenu; Humans; adaptivní imunita; Adaptive Immunity; COVID-19 Vaccines; Pneumonia, Viral; Pandemics; Coronavirus Infections; virové vakcíny; COVID-19